PERSONAL VALUES AND ATTRIBUTES PERCEPTION ABOUT COFFEE REGIONAL BRANDS IN LAVRAS - Pimenta, Marcio Lopes; Yokoyama, Marcos Hideyuki; Boas, Luiz Henrique de Barros Vilas; Moriguchi, Stella Naomi; Macedo, Juliana Flávia Palazzo da Costa (Revista de Administração da UFSM, 2011)
Regional food brands generate competitive differential because consumer links some desired attributes with a positive image of product's geographical origin. Such image influences the buying decision process, facing their perceptions about brand attributes and desired benefits in consuming products from these brands. On this view, this paper evidences the cognitive structure of consumers of roasted and milled coffee from Lavras' region, Minas Gerais State. Based upon in depth interviews, utilizing the laddering qualitative technique, it was made a hierarchic value map, that shows a connection of the regional brands to the attributes: ‘sensorial characteristics' , ‘from the region', ‘known brand', ‘lower price' and ‘pureness food'. From these attributes, the consumers believe in the possibility to reach personal values as: ‘self achievement', ‘personal and collective wellbeing', ‘happiness', ‘nostalgia', ‘life quality' and ‘longevity'.